Tobacco Exposure by Various Modes May Alter Proinflammatory (IL-12) and Anti-Inflammatory (IL-10) Levels and Affects the Survival of Prostate Carcinoma Patients: An Explorative Study in North Indian Population. (7th August 2014) - Dwivedi, Shailendra; Goel, Apul; Khattri, Sanjay; Mandhani, Anil; Sharma, Praveen; Pant, Kamlesh Kumar
Abstract : Objective . Inflammation is an important hallmark of all cancers and net inflammatory response is determined by a delicate balance between pro- and anti-inflammatory cytokines, which may be affected by tobacco exposure, so the present study was designed to explore the effect of various modes of tobacco exposure on interleukin-12 (IL-12) and interleukin-10 (IL-10) inflammatory cytokine levels and survival in prostate carcinoma (PCa) patients. Methods . 285 cancer patients and equal controls with 94 BPH (benign prostatic hyperplasia) were recruited; baseline levels of serum IL-12 and IL-10 were measured and analyzed in various tobacco exposed groups by appropriate statistical tool. Five-year survivals of patients were analyzed by Log-rank (Mantel-Cox) test (graph pad version 5). Results . The expression of serum proinflammatory (IL-12) and anti-inflammatory (IL-10) cytokines was correlated with tobacco exposed group as smokers, chewers, and alcohol users have shown significantly higher levels (P < 0.001 ) with significantly lower median survivals (27.1 months, standard error = 2.86, and 95% CI: 21.4–32.62); than nonusers. Stages III and IV of tobacco addicted patients have also shown significantly increased levels of IL-12 and IL-10. Conclusions . IL-12 and IL-10 seem to be affected by various modes of tobacco exposure and inflammation also affects median survival of cancer patients.